Tendency towards the fear of missing out - Lim, Zi Cheng Wesley (Curtin University, 2016)
The current study conducts a systematic review of current studies and works pertaining to the ‘Fear of Missing Out’ (FOMO), and to its effects within a marketing context. This is operationalized through the development of the Tendency towards the Fear of Missing Out (T-FOMO scale). The research model examines the effects of T-FOMO on consumer’s attitudes and intentions towards limited edition aspirational luxury products promoted with the use of explicitly expressed scarcity messages.